CONCEPTUALIZATION AND MEASUREMENT OF RELATIONSHIP VALUE: PRINCIPAL-RETAILER CONTEXT - Prasetya, Prita; Najib, Mukhamad; Soehadi, Agus W.; Djohar, Setiadi (Universitas Brawijaya, Indonesia, 2019)
The marketing literature reveals little agreement on the generalizability of relationship value scales that were developed in earlier works. Relationship value is more investigated methods founded on relationship marketing conception to describe and contribute better managing of the company. In this study, a relationship value scale was developed for a specific context in the principal-retailer relationship. Its involved definition of relationship value, methods for measuring relationship value, impact on sales collaboration, and business performance. These research assessed three alternative models of the dimension structure of relationship value construct then tested for reliability, validity, and confirmatory factor analysis. The result suggested that the four multi-item scales of relationship value developed showed evidence of reliability and validity. This method is recommended to measure relationship value. Further, the findings showed that relationship value has positive effects on both sales collaboration and business performance.